Limberg Flap Versus Primary Closure in the Treatment of Primary Sacrococcygeal Pilonidal Disease; A Randomized Clinical Trial - Khan, Parwez Sajad (Springer India, 2012)
Pilonidal sinus is a chronic intermittent disease, usually involving the sacrococcygeal area. This study was undertaken to compare the results of rhomboid excision followed by Limberg flap with that of excision and primary closure in patients with primary pilonidal sinus. A total of 120 patients with pilonidal disease were randomly divided into group A who underwent excision and primary closure (n = 60) and group B who underwent the rhomboid transposition flap procedure (n = 60). Length of hospital stay and postoperative complications in two groups were compared. Duration of hospital stay (P < 0.001) and time to resumption of work (P < 0.001) was less for group B, and postoperative complications were fewer in group B (P < 0.05). During follow-up of 2 years, no recurrence was detected in patients in group B, whereas five patients developed recurrence in group A (P = 0.02). Limberg flap procedure is better than the simple excision and primary closure for the management of sacrococcygeal pilonidal disease.